2003
DOI: 10.1016/s0257-8972(02)00563-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of an Al2O3-based refractory with CO2 and high power diode lasers for improved mechanical and chemical resistance characteristics

Abstract: Within both normal and corrosive (NaOH and HNO 3 ) environmental conditions, the wear rate and wear life characteristics of an Al 2 O 3 -based refractory were greatly enhanced by means of CO 2 and high power diode laser (HPDL) surface treatment. Such improvements are attributed to the fact that after laser treatment, the microstructure of the Al 2 O 3 -based refractory was altered from a porous, randomly ordered structure, to a much more dense and consolidated structure that contained fewer cracks and porositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The material conservation has become an important concern due to ever increasing global competition [1]. Corrosion is defined as the deterioration of materials by reaction with the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The material conservation has become an important concern due to ever increasing global competition [1]. Corrosion is defined as the deterioration of materials by reaction with the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The surface treatment of an aluminabased refractory was examined by Lawrence and Li (1). The surface treatment of an aluminabased refractory was examined by Lawrence and Li (1).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that laser treated surface resulted in high microhardness and reduced surface roughness values. Laser surface treatment of alumina based refractory was carried out by Lawrence and Li [5]. They indicated that the use of high power diode lasers improved the depth of treated layer and resulted in enhanced wear performance of the surface.…”
Section: Introductionmentioning
confidence: 99%